Comparative analysis of atherosclerotic disease in the carotid and femoral arteries - Hurst, KV (2024)
Introduction Peripheral arterial occlusive disease (PAOD) is a common vascular pathology affecting up to 60% of the population over 85 years. It often presents in a triad of atherosclerotic disease, alongside myocardial ischaemia and cerebrovascular accident. Best medical therapy is used in the treatment for all three; and shows a 16% reduction in stroke events and 10-40% reduction in cardiac events. POAD has not been subject to the same level of research, and primary analysis indicates little reduction in deterioration or amputation rates for 30 years. Methods The study aimed to use in vivo and ex vivo analysis of carotid and femoral atherosclerotic plaque from patients enrolled in the OxPVD study. Each participant underwent pre-operative carotid and femoral (ipsilateral) MRI scans, and ex vivo plaque was analysed using micro CT, micro MRI and histological staining. Comparative analysis was completed for carotid versus femoral atherosclerosis. Results Results from this study have shown that despite risk factor modification, overall outcomes of patients with POAD remain unchanged. Patients do however present to the services 7 years older. Secondly, novel MRI DANTE sequences can successfully characterise femoral atherosclerotic plaque in vivo.